THE INFLUENCE OF MACROECONOMIC VARIABLES ON PROFITABILITY SHARIA COMMERCIAL BANKS IN INDONESIA (Case Study at Bank Muamalat Indonesia for the 2007-2021 period) - Charisma Indah Pratiwi; Roosaleh Laksono (Jurnal Ekonomi, 2023)
This study aims to find out about the effect of macroeconomic variabel on the profitability of Bank Muamalat Indonesia for the 2007-2021 period. The object of research in this study is Bank Muamalat Indonesia for the 2007-2021 period. The research method used in this research is the documentation study method. The population in this study is report on inflation, exchange rate, BI Rate, money supply and annual ROA report at Bank Muamalat Indonesia for the 2007-2021 period which has been published by Bank Muamalat Indonesia. Statistical test using multiple linear regression analysis were processed using Eviews 12, with a significant level of 5%. The result of this study indicate that the Inflation and BI Rate partially influences profitability of Bank Muamalat Indonesia, while the Exchange rate and money supply partially has no effect on profitability of Bank Muamalat Indonesia, and inflation, exchange rate, BI Rate, and money supply simultaneously influences profitability of Bank Muamalat Indonesia.